2011
DOI: 10.1371/journal.pone.0018085
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Caloric Restriction on Constitutive Expression of NF-κB in an Experimental Mouse Astrocytoma

Abstract: BackgroundMany of the current standard therapies employed for the management of primary malignant brain cancers are largely viewed as palliative, ultimately because these conventional strategies have been shown, in many instances, to decrease patient quality of life while only offering a modest increase in the length of survival. We propose that caloric restriction (CR) is an alternative metabolic therapy for brain cancer management that will not only improve survival but also reduce the morbidity associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 100 publications
(153 reference statements)
1
49
0
1
Order By: Relevance
“…The metabolic shift from glucose metabolism to ketone body metabolism creates an anti-angiogenic, anti-inflammatory and proapoptotic environment within the tumor mass (192,(195)(196)(197)(198)(199). The general concept of a survival advantage of tumor cells over normal cells occurs when fermentable fuels are abundant, but not when they are limited (20).…”
Section: Exploiting Mitochondrial Dysfunction For the Metabolic Managmentioning
confidence: 99%
“…The metabolic shift from glucose metabolism to ketone body metabolism creates an anti-angiogenic, anti-inflammatory and proapoptotic environment within the tumor mass (192,(195)(196)(197)(198)(199). The general concept of a survival advantage of tumor cells over normal cells occurs when fermentable fuels are abundant, but not when they are limited (20).…”
Section: Exploiting Mitochondrial Dysfunction For the Metabolic Managmentioning
confidence: 99%
“…CR and RKD will simultaneously target multiple metabolic pathways in tumor cells without causing adverse effects or toxicity to normal cells (Marsh et al, 2008a;Seyfried et al, 2010b;Shelton et al, 2010b;Zuccoli et al, 2010). The systemic energy transition from glucose to ketones will reduce inflammation in the tumor microenvironment, thus reducing progression as we recently described (Mulrooney et al, 2011).…”
Section: Synergistic Interaction Of Rkd and 2-deoxyglucose (2-dg)mentioning
confidence: 96%
“…We showed that calorie restriction; (a) reduces the phosphorylation and degree of transcriptional activation of the NF-B-dependent genes COX-2 and AIF-1 in CT-2A tumor tissue and, (b) reduces expression of pro-inflammatory markers lying downstream of NF-B, e.g., macrophage inflammatory protein-2 (MIP-2) (Mulrooney et al, 2011). On the whole, we showed that the NF-B inflammatory pathway is constitutively activated in the CT-2A astrocytoma and that CR targets this pathway and inflammation.…”
Section: Calorie Restriction Targets Nuclear Factor B (Nf-b) and Is Amentioning
confidence: 99%
See 2 more Smart Citations